Déterminants d'une expérience inclusive de loisir dans des ateliers créatifs au sein de bibliothèques publiques. Issue 2 (4th May 2021) - Poulin, Valérie; Carbonneau, Hélène; Mostefa-Kara, Leila; Porcedda, Aude; Guibourgé, Delphine; Therriault, Pierre-Yves; Reichhart, Frédéric
Abstract : Public libraries are becoming a third place dedicated to community life, with new spaces promoting exchanges and co-creation, such as Fab Labs (digital creation activities) and Art Hives (artistic activities). This participatory research, using a Living Lab approach, aimed to identify key elements that promote inclusive leisure experiences of people living with disabilities in creative workshops. Data were collected during four Fab Lab workshops and four Art Hives artistic workshops in two public libraries, with eight participants living with disabilities, using video recordings, photos, and two focus groups. Findings suggest that inclusive leisure experiences involve the physical access to places and activities (e.g., signalling of accessible entrances); opportunities for experiencing positive interactions (e.g., quality of reception on arrival); and engagement in meaningful activities. This experience is built before (e.g., organizing transport), during and after the activity. Suggestions for concrete actions for the various stakeholders are derived from these results.